Being and Corona: Contemporary Philosophy in the Face of the Unexpected - Al-Jaff, Karim Hussein (Al-Adab Journal, 2021)
This paper entitled Being and Corona: Contemporary Philosophy in the Face of the Unexpected seeks to present a new vision for the act of philosophical thought, after the Corona event, with which we are facing a new stage of challenges that require the discovery of new mechanisms that stimulate the act of thought to create new frameworks for thinking in environments of the unexpected. Ancient philosophy plunges into the depths of being in order to search for an origin, principle, or goal for beings and events in the context of the cosmos, and through the web of spider metaphysics that absorbs its vitality and makes it outside the stream of time and history by establishing a preconceived plan for play, but contemporary philosophy today does not develop plans and preconceptions. For events, but leave those plans to the circumstances in a timely manner that will determine the quality of the appropriate concept for his creativity, due to the randomness of the current reality, which is characterized as far from balance, that is, it is a chaotic environment nonlinear.